(untitled) (Global Journal of Science Frontier Research, 2023)
At the present energy independence along with global warming for high mountain regions is quite significant issues Impact of climate change on water resources which accompanied by melting glaciers and snow cover leads water shortage About 94 generated energy in Kyrgyzstan produced from water resources Shortage of water resources created for society in sustainable development of economy and challenge of severely ecological consequences Therefore one of the adaptation measures to the climate change is looking for alternative way with usage of renewable energy For ensuring of energy safety of the population of Kyrgyzstan as a priority should be taking account usage of solar biomass and geothermal energy